Penegakan Hukum Pelaku Tindak Pidana Kehutanan oleh Penyidik Pegawai Negeri Sipil Kehutanan di Balai Taman Nasional Meru Betiri - Wayan Budiarta (JURNAL RECHTENS, 2016)
The probe is the beginning stage of the examination by the official designated by law as a violation of the law. Therefore, in the investigation phase can already be set setatusnya as suspects when their initial evidence sufficient or at least two items of evidence legal proof. Implementation of an investigation of law enforcement efforts in tackling forest crime. Law enforcement against forest crime by a civil servant investigators (PPNS) forest in Meru National Park Betiri going well and always based on the existing rules. Law enforcement is not only against the perpetrators of the messengers but also the actor intellectual where the success of uncovering some cases such as illegal logging in the region of Meru National Park Betiri being dragged to court against both the perpetrators, fences and participate or to have committed the crime of forestry.